Estimation of transport accessibility of the Capital Economic Region - Matiychyk, Olena; Babenko Andriі; Yanovsky, Peter; Sulyma, Liudmyla (Eastern-European Journal of Enterprise Technologies, 2017)
The methodology for estimation of potential transport accessibility of the region, which requires merely open data, was identified. The choice of the Capital Economic Region as the region for estimation of transport accessibility was validated. The study solved the problem of adapting the foreign approach to calculation of potential transport accessibility of the Capital Economic Region. The highlight of the given research is the application of Euclidean distance between the cities (nodes) and the total of activity types available in the destination node as the initial data for estimating transport accessibility. The proposed methodology of potential road transport accessibility estimation of the region enables revealing of the potential deficiencies in the transport infrastructure of the region. This is provided by the special feature of the methodology which is based on the suggested equation for calculation of transport accessibility and the scale developed in the paper. The scale contains seven levels of potential transport accessibility of the Capital Economic Region and it enables quantitative evaluation of the transport accessibility values for the given city (node) in relation to the set of other cities (nodes). Thus, the degree of spatial separation of the cities related to the regional center can be defined. The given methodology can be applied for other regions of Ukraine to evaluate current efficiency of the road transportation network. It is recommended to devise a new scale for evaluating potential transport accessibility while applying the proposed methodology to another region. Other possible applications of the methodology include urban planning, transport planning, creating and / or developing regional transport systems.